2019
DOI: 10.14710/nmjn.v9i2.22989
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Knowledge, Attitudes, Skills, and Glucose Control in Type-2 Diabetic Patients through EMAS Interventions

Abstract: Background: Diabetes Mellitus (DM) is a chronic and non-communicable disease that has serious impacts. Previous studies have focused on a single intervention in the management of DM. Therefore, EMAS (education, nutrition management, physical activities, and stress management) interventions are proposed to convey the pillars of diabetes mellitus as endorsed by the Indonesian Ministry of Health.Purpose: This study aimed to analyze the effects of EMAS interventions on the knowledge, attitudes, skills, and glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The family's ability to provide care for family members who suffer from DM has increased by using supportive group therapy interventions (Shama et al, 2020). Another study conducted a diabetes education program without involving the family for six months; the study revealed positive changes in the respondents' diet plans, glucose monitoring, regular medication-taking, physical activities, and stress levels (Andriyanto et al, 2019). Other researchers have demonstrated glycemic control through effective self-management education (DSME) (Abdulah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The family's ability to provide care for family members who suffer from DM has increased by using supportive group therapy interventions (Shama et al, 2020). Another study conducted a diabetes education program without involving the family for six months; the study revealed positive changes in the respondents' diet plans, glucose monitoring, regular medication-taking, physical activities, and stress levels (Andriyanto et al, 2019). Other researchers have demonstrated glycemic control through effective self-management education (DSME) (Abdulah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts made by health services emphasize the overall management of DM through the Social Support Management of Diabetes (SoSMeD) approach. Community and family-based approaches, namely, Community as Partner, Family-Centered Nursing, Maglaya, Health Promotion Model toward increasing self-awareness, self efficacy, and behavior change that look at the biological factors of type 2 diabetes patients, iterpersonal health factors, health threats, and service provider factors, such as non-communicable disease services [12]. Families should support those who experience DM to maintain optimal health status and independence [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Families who do not understand how to care for people with DM will feel the burden of caring, so training is needed to fulfill basic needs in people with DM at home. Besides, families must increase the motivation of people with DM to routinely take medical check-ups in the nearest service [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the chronic nature of diabetes, the disease may pose serious complications if poorly managed. Patients' active involvement in their diabetes care has a pivotal role in the prognosis of the disease (Andriyanto et al, 2019;Holtz & Lauckner, 2012;Mulvaney et al, 2012). Patients' contribution can only be achieved if patients are fully informed; therefore, delivering a diabetes education program to promote self-care in managing their disease termed self-management is crucial (Funnell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%